SYSTEMIC LUPUS ERYTHEMATOSUS AND DENTISTRY - Monteiro, Yngrid; Possatto, Adriano; Borges, Yara; Martinelli, Yasmin (Health and Society, 2022)
Introduction: Systemic lupus erythematosus (SLE) can be described as a heterogeneous, multisystemic autoimmune disease characterized by the production of autoantibodies against several cell constituents. Objective: To characterize the relationship between systemic lupus erythematosus and dentistry, explaining the means for its diagnosis and treatment. Method: For the composition of this work, we use the investigation method based on a bibliographic survey of sources (physical and digital) relevant to the theme addressed here. Conclusion: When early detection of SLE by the dentist, it is possible to institute, case by case, a specific immunosuppressive therapy that enables a better prognosis.